1998
DOI: 10.1183/09031936.98.11061222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the polymerase chain reaction in the diagnosis of extrapulmonary tuberculosis

Abstract: aaMicroscopy with the auramine or Ziehl-Neelsen (ZN) stain is frequently negative in cases of extrapulmonary tuberculosis (TB). This means that treatment may be started and continued until the culture results confirm or refute the diagnosis at least 3 weeks later. The polymerase chain reaction (PCR), which permits direct identification of the Mycobacterium tuberculosis complex [1, 2] is more sensitive than microscopy, has a much lower detection limit and gives results within 24 h of receipt of the sample. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…However, the diagnostic yield of PCR in HIV-seronegative patients suffering from extrapulmonary TB was very low in peripheral blood, bone marrow, urine, and pleural or pericardial fluid [13,14,25,26]. Furthermore, earlier reports failed to demonstrate the validity of PCR amplification for diagnosis FUO in HIV-negative cases of extrapulmonary TB [13,25,26]. Although our study included a relatively small number of FUO patients, it nevertheless demonstrated the high sensitivity of the applied PCR protocol in bone marrow and/or in samples obtained from suspected tissues of Mycobacterium contamination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic yield of PCR in HIV-seronegative patients suffering from extrapulmonary TB was very low in peripheral blood, bone marrow, urine, and pleural or pericardial fluid [13,14,25,26]. Furthermore, earlier reports failed to demonstrate the validity of PCR amplification for diagnosis FUO in HIV-negative cases of extrapulmonary TB [13,25,26]. Although our study included a relatively small number of FUO patients, it nevertheless demonstrated the high sensitivity of the applied PCR protocol in bone marrow and/or in samples obtained from suspected tissues of Mycobacterium contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported the positivity of the M. tuberculosis complex by PCR targeting the IS6110 element in specimen wise distribution of the M. tuberculosis complex in EPTB. Tiwari et al, [22] Maurya A K et al, [23] S. Nagesh et al, [26] Portillo -Gomez L, et al, [27] Kolk, AHJ et al, [28] Sekar B et al, [29] showed the detection of the M. tuberculosis complex in the pleural fluid by PCR results as summarized in Table 4. In our study we found 70% positivity in PCR targeting the IS6110 element in pleural fluid specimens.…”
Section: Discussionmentioning
confidence: 99%
“…35 In the present study, PCR exhibited greater sensitivity than microscopy and the culture, and could facilitate therapeutic decisions for patients with a clinical suspicion of ETB; as was found by other authors. [36][37][38] For diagnosis of GUTB, although a high index for clinical suspicion is necessary, 39 PCR can be useful for cases in which bacteriologic and clinical diagnoses of TB are not conclusive. 40 We found PCR to be a very rapid diagnostic method for GUTB.…”
Section: Discussionmentioning
confidence: 99%